Comparison of polyelectrolyte and sodium dodecyl benzene sulfonate as dispersants for multiwalled carbon nanotubes on cotton fabrics for electromagnetic interference shielding. Issue 15 (14th March 2014) - Zou, Lihua; Yao, Lan; Ma, Ying; Li, Xiangpeng; Sailimujiang, Shalayiding; Qiu, Yiping
ABSTRACT Cotton fabrics with multiwalled carbon nanotubes (MWCNTs) dispersed by Nafion, a polyelectrolyte, and sodium dodecyl benzene sulfonate (SDBS), a surfactant, were prepared for electromagnetic interference (EMI) shielding. The fabrics were characterized by scanning electron microscopy and vector network analysis. The fabrics with the Nafion–MWCNT coating possessed a better shielding efficiency (SE) than those with the SDBS–MWCNT coating because of a more uniform dispersion of MWCNTs, which improved the electrical conductivity and EMI shielding properties. The maximum SE value of the fabric reached 11.48 dB, and the specific SE was 39.6 dB cm3/g. The reflectivity and absorptivity were calculated separately to determine the main mechanism of EMI shielding. The absorptivity was 68.6% at 12 GHz for the Nafion–MWCNT‐coated fabric; this showed that the dominant mechanism of EMI shielding for the treated fabrics was absorption. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40588.